The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 2016 CHI Conference on Human Factors in Computing Systems 2016
DOI: 10.1145/2858036.2858037
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Steering Time Difference between Narrowing and Widening Tunnels

Abstract: The performance of trajectory-based tasks is modeled by the steering law, which predicts the required time from the index of difficulty (ID). This paper focuses on the fact that the time required to pass through a straight path with linearly-varying width alters depending on the direction of the movement. In this study, an expression for the relationship between the ID of narrowing and widening paths has been developed. This expression can be used to predict the movement time needed to pass through in the oppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 20 publications
5
17
0
Order By: Relevance
“…Tu investigated the difference in stroke gestures between the finger and the pen [17]. Cutting behavior using scissors was modeled in [18]. Yamanaka modeled the cutting behavior by scissors [19].…”
Section: Related Workmentioning
confidence: 99%
“…Tu investigated the difference in stroke gestures between the finger and the pen [17]. Cutting behavior using scissors was modeled in [18]. Yamanaka modeled the cutting behavior by scissors [19].…”
Section: Related Workmentioning
confidence: 99%
“…Curves have many deformations according to the curvature, and [10] researchers have investigated the Steering law that adapts to them. Additionally, shape-based differences have been investigated [16,13]. [14] modeled the cutting behavior by scissors.…”
Section: Related Workmentioning
confidence: 99%
“…Participants were instructed to perform the required operation as quickly and accurately as possible. We referred to the measurement method that many researchers have used for the series of processes and system instructions [2,13].…”
Section: System For Measuring Skill Levelmentioning
confidence: 99%
“…Equation 2 was derived as the integral of infinitesimal constant-width tunnels. However, Yamanaka and Miyashita indicated that the ID for the opposite direction could be calculated using the same formula of Equation 2 [24]. Because the actual MTNT was greater than MTWT, they proposed a corrected model that expresses the ID difference, IDGap, between narrowing and widening straight tunnels:…”
Section: Steering Lawmentioning
confidence: 99%
“…In this study, using a direct-input stylus, we discuss the scale effects in the steering time difference between narrowing and widening linear tunnels. Quite recently, Yamanaka and Miyashita found that MT for a narrowing tunnel (MTNT) is significantly greater than MT for a widening tunnel (MTWT), and they derived a difficulty difference model called IDGap [24]. The validity of this model was confirmed by an experiment using tunnels of amplitude A between 61.2 and 122.4 mm and width W between 2.2 and 10.4 mm requiring primarily wrist movements with a particular level of forearm extension.…”
Section: Introductionmentioning
confidence: 98%